Analysis of Students' Difficulties in Solving Problems on Calculating Mixed Fraction Operations for Class V State Elementary School 003 Batu Bagan - Vika Sari Handayani; Witri, Gustimal (Education Generation Journal, 2024)
This research aims to analyze students' difficulties and the factors that cause students' difficulties in solving mixed fraction calculation operations questions for class V at SD Negeri 003 Bagan Batu. This research uses descriptive quantitative methods. Data collection techniques use tests and interviews. The data analysis technique is based on Lerner's three aspects of mathematics learning difficulties, namely concepts, skills and problem solving. The results of the research data found that students experienced concept difficulties, namely 28.64%, skill difficulties 52.12% and problem solving difficulties 60.91%. The factors that cause students to experience difficulties are internal factors and external factors. Internal factors originating from students include not knowing how to solve questions, low level of student concentration, low student motivation to learn, lack of interest in the lesson. External factors are factors that come from outside the student, such as school environmental factors and family factors